Spirit’s Self-Knowledge, History, and the Absolute (Revista Eletrônica Estudos Hegelianos, 2018)
The paper offers an answer to John McDowell’s question of why it matters to Hegel that Geist has a history. Spirit’s content is revelation (Enc. § 383), and spirit realizes itself as what it is – revelation – by unfolding into two dimensions: a finite and an infinite subject. The infinite subject successively gives new forms of thinking to the finite subject, and this succession is history. This is shown more concretely with regard to the historical development of (philosophical) conceptions of self-consciousness from Descartes via Kant to Hegel. From this an overall picture of Hegel’s philosophy of spirit emerges through which its culmination in absolute spirit and, in particular, religion becomes conceivable and according to which there is a leap between Hegel’s philosophy and the pagan world. Thus, the paper is directed against two widespread tendencies in current readings of Hegel: the tendency to cut off or downplay absolute spirit in favor of subjective and objective spirit, and the tendency to assimilate Hegel’s philosophy of spirit to Aristotle’s philosophy of soul and life.